Agile Leadership in Crisis Management : Lessons from the COVID-19 Pandemic for Sustainable Business Practices - Amina El Alaoui; Nadia Yassir; Samira Said (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
The COVID-19 pandemic has presented unprecedented challenges, requiring organizations to adapt swiftly and navigate through uncertainty. Agile leadership has emerged as a critical factor in effectively managing crises and ensuring business sustainability. This study explores the role of agile leadership in crisis management, emphasizing the lessons learned from the COVID-19 pandemic. By analyzing case studies and best practices, this paper highlights the key attributes of agile leaders, such as adaptability, resilience, and the ability to foster innovation under pressure. Furthermore, it examines how agile leadership principles can be applied to develop sustainable business practices in a volatile and complex environment. The findings of this study provide actionable insights for organizations aiming to enhance their crisis response capabilities and promote long-term sustainability.